The Psychological Benefits of COVID-19 Vaccination - My Nguyen (Advances in Public Health)
This study evaluates the extent to which COVID-19 vaccination affects population mental health. Exploiting the within-state and within-survey week variation in the number fully vaccinated per 10 million people, I uncover the favorable effects of vaccination on individuals’ psychological well-being. Particularly, a 100% increase in the number fully vaccinated per 10 million people makes individuals 0.24, 0.23, 0.12, and 0.14 percentage points less likely to experience anxiety, worry, displeasure, and depression on a daily basis, respectively. The probability of having at least one of the four symptoms (anxiety, worry, displeasure, and depression) every day also reduces by 0.27 percentage points. The study calls for the expansion of vaccine coverage, especially for disproportionately affected communities.